Mapping Television Shows that are of Favored by Elementary School Students - Atiqa Sabardila; Markhamah Markhamah; Zainal Arifin; Hari Kusmanto; Lathifah Nurul Hidayah; Anita Dewi Kurniasari; Duwi Saputro (Universitas Pendidikan Ganesha, 2021)
The various television shows can now be easily accessed by children for 24 hours without the need for parental controls. Television shows that are presented are of various types, ranging from educational shows, cartoons to soap operas. This article aims to map out television shows that are of favored by elementary school students. The approach of this research is qualitative descriptive. The subjects of this study were elementary school students from grade I to grade VI. The data of this study were collected by using interview and observation methods. The data analysis of this study used an interactive method. The results of this study shows that television shows that are of favored by elementary school students are: Spongebob, Upin & Ipin, Kamen Rider Ex-Aid, Doraemon, Munki and Trunk, Si Bolang, On The Spot, Anak Langit, Tukang Ojek Pengkolan. It can be concluded that television shows that are favored by elementary school students are cartoon shows that have the power of imagination and creativity. There is a need for parental control when children watch television, especially on television shows in which the are elements of violence and bullying.